2002
DOI: 10.1159/000065567
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Primary Renal Lymphoma

Abstract: A case of primary renal lymphoma (PRL) in a 78-year-old man is reported. The tumor was found by computed tomography during a check-up for hematuria and weight loss. Histologic and immunohistochemical analyses of this tumor revealed features typical of low-grade lymphoma with localized amyloid deposition. PRL is a rare disease and only a few cases have been reported previously. To our knowledge, there have been no other reports of PRL with localized amyloid deposition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 7 publications
0
8
0
Order By: Relevance
“…Dimopoulus et al [11] showed that 3% of the renal masses that had radiological findings were suggestive of renal cell carcinoma diagnosed finally as primary renallymphoma.ThetumorcanalsobefoundbyCTduring a check-up for hematuria and weight loss [12]. Our 4 cases werecharacterizedbyasolitaryrenalmassormultiplerenal masses.Whilethefirstandthethirdcasewerediagnosedas primary renal lymphoma by nephrectomy, the second case wasdiagnosedbyopenexcisionalrenalbiopsyundergeneral anesthesia.Allofourcaseswereinitiallyacceptedasarenal cellcarcinomaandthereforereferredtotheurologyclinic.…”
Section: Discussionmentioning
confidence: 99%
“…Dimopoulus et al [11] showed that 3% of the renal masses that had radiological findings were suggestive of renal cell carcinoma diagnosed finally as primary renallymphoma.ThetumorcanalsobefoundbyCTduring a check-up for hematuria and weight loss [12]. Our 4 cases werecharacterizedbyasolitaryrenalmassormultiplerenal masses.Whilethefirstandthethirdcasewerediagnosedas primary renal lymphoma by nephrectomy, the second case wasdiagnosedbyopenexcisionalrenalbiopsyundergeneral anesthesia.Allofourcaseswereinitiallyacceptedasarenal cellcarcinomaandthereforereferredtotheurologyclinic.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrasonography of the reported cases of PRNHL in the kidney shows a hypoechoic mass. 10 Typical CT patterns in PRNHL are the presence of multiple and bilateral hypovascular renal masses (reported in 60% of cases), renal invasion from contiguous retroperitoneal disease (reported in 25%–30% of cases), presence of peri-renal disease, and diffuse renal infiltration (reported in 20% of cases). Atypical findings include spontaneous hemorrhage, necrosis, heterogeneous attenuation, cystic transformation, and calcification.…”
Section: Resultsmentioning
confidence: 99%
“…9 The diagnosis of PRNHL can be made when there is a renal mass in the absence of a leukemic blood picture and no evidence of extra-renal lymphoma in the other organs or lymph nodes as the first presentation. 10 PRNHL most commonly occurs in adults. It is common to be bilateral in contrast to other adult renal tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations